2011
DOI: 10.1103/physrevlett.107.145305
|View full text |Cite
|
Sign up to set email alerts
|

Metastability in Spin-Polarized Fermi Gases

Abstract: We study the role of particle transport and evaporation on the phase separation of an ultracold, spinpolarized atomic Fermi gas. We show that the previously observed deformation of the superfluid paired core is a result of evaporative depolarization of the superfluid due to a combination of enhanced evaporation at the center of the trap and the inhibition of spin transport at the normal-superfluid phase boundary. These factors contribute to a nonequilibrium jump in the chemical potentials at the phase boundary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…The latest experiments by the group at Rice indicate that their deviating experimental results are caused by spin currents in the trap that create a long lived metastable state with a deformed superfluid core [78]. These experiments confirm the theoretical proposal of Parish and Huse [151], who showed that this metastable state could arise due to the elongated trap geometry, in which evaporation occurs predominantly from the trap center.…”
Section: Experimental Overviewsupporting
confidence: 65%
See 2 more Smart Citations
“…The latest experiments by the group at Rice indicate that their deviating experimental results are caused by spin currents in the trap that create a long lived metastable state with a deformed superfluid core [78]. These experiments confirm the theoretical proposal of Parish and Huse [151], who showed that this metastable state could arise due to the elongated trap geometry, in which evaporation occurs predominantly from the trap center.…”
Section: Experimental Overviewsupporting
confidence: 65%
“…Later, the imbalanced atomic Fermi gas was also experimentally studied at ENS, where Nascimbène et al accurately measured the collective modes [73] and the equation of state of the imbalanced Fermi gas [74,75]. In most recent experimental studies, also nonequilibrium aspects of the imbalanced Fermi gas are considered, such as spin transport [76,77] and metastable states [78].…”
Section: This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of phase separation in spin-imbalanced Fermi gases were obtained at Rice and MIT by direct in-situ imaging of the density distributions [17][18][19], and by imaging the distributions in time-of-flight [20]. The distributions in the Rice experiment were out-of-equilibrium due to an evaporative depolarization mechanism at work in their highly elongated confining potential [21,22], and could not, therefore, be compared with distributions calculated assuming equilibrium. Density profiles obtained by the MIT group at unitarity and on the BEC side of resonance [23] agree quantitatively with the theory of Bertaina and Giorgini (BG) computed using quantum Monte Carlo (QMC) and the LDA [24].…”
mentioning
confidence: 99%
“…The experiments on the phase diagram of polarized 1 Fermi gases done at MIT [13][14][15] and Paris [16] can be well understood within the LDA. Only in an experiment at Rice University [17], clear deviations from LDA were observed, but they were later shown to correspond to a metastable non-equilibrium configuration of the atomic cloud [18,19].…”
Section: Introductionmentioning
confidence: 99%